Optimization of Extracted Phenolic Compounds from Oregano through Accelerated Solvent Extraction Using Response Surface Methodology - Christina Panagiotidou; Elisavet Bouloumpasi; Maria Irakli; Paschalina Chatzopoulou (Engineering Proceedings, 2024)
The current research focuses on the optimization of accelerated solvent extraction, a potential alternative to conventional solvent extraction, for the extraction of phenolics from Greek oregano. The response surface methodology based on central composite design was used to optimize methanol concentration (X1, 40–80%), extraction time (X2, 3–9 min, 3 cycles), and extraction temperature (X3, 60–140 °C). Under the optimal extraction conditions (methanol concentration of 74%, extraction time of 9 min, extraction temperature of 140 °C), the experimental values for extraction yield (%), total phenolic (TPC) and flavonoid contents (TFC), and antioxidant capacity matched those predicted, therefore validating the model adequately. The oregano extracts were rich in phenolic compounds, with rosmarinic acid and salvianolic acid B being the most prevalent phenolic components. The results obtained revealed that ASE can be utilized for the extraction of bioactive compounds, and there are advantages to preserving phenolic content if optimization is applied.